Characterization of GM-CSF-inhibitory factor and Uracil DNA glycosylase encoding genes from camel pseudocowpoxvirus. (June 2015) - Nagarajan, G.; Swami, Shelesh Kumar; Dahiya, Shyam Singh; Narnaware, S.D.; Mehta, S.C.; Singh, P.K.; Singh, Raghvendar; Tuteja, F.C.; Patil, N.V.
Highlights: Two genes viz., GIF and UDG, of camel PCPV from India were cloned and sequenced for the first time. The presence of the mutation in GIF of camel PCPV does not alter the biological activity theoretically. Phylogenetic tree analysis supports that camel PCPV is closer to PCPV reference strains and ORFV. Abstract: The present study describes the PCR amplification of GM-CSF-inhibitory factor (GIF) and Uracil DNA glycosylase (UDG) encoding genes of pseudocowpoxvirus (PCPV) from the Indian Dromedaries ( Camelus dromedarius ) infected with contagious ecthyma using the primers based on the corresponding gene sequences of human PCPV and reindeer PCPV, respectively. The length of GIF gene of PCPV obtained from camel is 795 bp and due to the addition of one cytosine residue at position 374 and one adenine residue at position 516, the open reading frame (ORF) got altered, resulting in the production of truncated polypeptide. The ORF of UDG encoding gene of camel PCPV is 696 bp encoding a polypeptide of 26.0 kDa. Comparison of amino acid sequence homologies of GIF and UDG of camel PCPV revealed that the camel PCPV is closer to ORFV and PCPV (reference stains of both human and reindeer), respectively.